Penerapan Sak EMKM dan Analisis Kinerja Keuangan : Studi Kasus pada UMKM Busana Rose - Alif Damayanti; Annisa Maulidina; Friska Valentina Moniaga; Siti Rahma Munawaroh; Fitrina Kurniati (Akuntansi, 2024)
This research was conducted at one of the Micro, Small and Medium Enterprises (MSMEs) in Bekasi, namely the Busana Rose which provides various types of clothing. The aim of this research is to analyze the application of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) to MSMEs, assist with financial recording in accordance with SAK EMKM for the period January to September 2024, and analyze financial reports. conditions and formulate strategic recommendations to increase the effectiveness of implementing SAK EMKM. The method used in this research is a qualitative descriptive method. Data collection was carried out through observation, documentation and interviews. For data analysis, financial ratio analysis is used which includes calculating liquidity, solvency and profitability ratios. The research results show that based on the analysis of liquidity, solvency and profitability ratios, Busana Rose MSMEs show good financial performance, with ratio values above the industry average. However, Return On Asset (ROA) analysis shows less than satisfactory results, with an ROA value of 1.8%, lower than the industry average of 2%. Therefore, it is recommended to the pemiliks of Rose Busana MSMEs to improve asset management, especially receivables, regularly check trade inventory to control the number of goods that have not been sold for a long time, and utilize online promotional media to maximize the profits obtained.